Redefine Malaysian university of the future business models in the digital age: humanizing higher education program for orphans and youth from poor families - Zailan, Siti Nur Syamimi; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2019)
This paper takes a gander in the past, current and future computerized change plan for the Digital transformation. There are unprecedented challenges in the future of higher education. Why will we get people ready to bring about sustainable change that would also increase the personal satisfaction of individuals? For every field of human life, the need to consider Sustainable Development Goals is a profound fact. As a result, knowledge collection cannot be left to risk and higher education institutions should be held accountable. Higher education is generally assumed to have a two-fold objective: to provide job opportunities and to create awareness. Both have a shared goal of improving the quality of our lives. Humanizing education should be modified within the university in order to maintain sustainability and remain important with the universities' future goal. For those who are poor, vulnerable and unemployed, youth issues are frequently encountered. Therefore, this paper aims to provide a conceptual business model of humanizing education including an eLearning, mentoring program and eMarketplace to support orphans and youth from poor (B40) families in Gombak District, Selangor. The paper presents the business models, methodologies, and strategies to turn the university from a non-described organization into a dynamic organization with relevant knowledge, skills, and human qualities such as honesty and ethical efficiency.